'I can no longer do my work like how I used to': a mixed methods longitudinal cohort study exploring how informal working mothers balance the requirements of livelihood and safe childcare in South Africa - Christiane Horwood; Rachael Hinton; Lyn Haskins; Silondile Luthuli; Sphindile Mapumulo; Nigel Rollins (BMC, 2021)
Abstract Background Returning to work after childbirth is challenging for working mothers. Childcare quality may have lifelong effects on children's health, development and cognitive function. Over 60% of working women globally are informal workers without employment or maternity protection, but little is known about how these women care for their children. Methods We conducted a mixed-methods longitudinal cohort study among informal women workers in Kwazulu-Natal, South Africa between July 2018 and August 2019. Participants were followed up from late pregnancy until they had returned to work. We conducted structured quantitative interviews and in-depth qualitative interviews at different time points: before and after the baby was born, and after returning to work. Subsequently, a photovoice activity was conducted with groups of participants to explore the childcare environment. We employed narrative thematic analysis for qualitative data and descriptive analysis for quantitative data. Results 24 women were recruited to participate. Women returned to work soon after the baby was born, often earlier than planned, because of financial responsibilities to provide for the household and new baby. Women had limited childcare choices and most preferred to leave their babies with family members at home, as the most convenient, low cost option. Otherwise, mothers chose paid carers or formal childcare. However, formal childcare was reported to be poor quality, unaffordable and not suited to needs of informal workers. Mothers expressed concern about carers' reliability and the safety of the childcare environment. Flexibility of informal work allowed some mothers to adapt their work to care for their child themselves, but others were unable to arrange consistent childcare, sometimes leaving the child with unsuitable carers to avoid losing paid work. Mothers were frequently anxious about leaving the child but felt they had no choice as they needed to work. Conclusion Mothers in informal work had limited childcare options and children were exposed to unsafe, poor-quality care. Maternity protection for informal workers would support these mothers to stay home longer to care for themselves, their family and their baby. Provision of good quality, affordable childcare would provide stability for mothers and give these vulnerable children the opportunity to thrive.